The Master Guide to Controllers' Best Practices, 2nd Edition - Stattler, Elaine; Grabel, Joyce (Wiley, 2020)
The essential guide for today's savvy controllers Today's controllers are in leadership roles that put them in the unique position to see across all aspects of the operations they support. The Master Guide to Controllers' Best Practices, Second Edition has been revised and updated to provide controllers with the information they need to successfully monitor their organizations' internal control environments and offer direction and consultation on internal control issues. In addition, the authors include guidance to help controllers carryout their responsibilities to ensure that all financial accounts are reviewed for reasonableness and are reconciled to supporting transactions, as well as performing asset verification. Comprehensive in scope the book contains the best practices for controllers and: Reveals how to set the right tone within an organization and foster an ethical climate Includes information on risk management, internal controls, and fraud prevention Highlights the IT security controls with the key components of successful governance Examines the crucial role of the controller in corporate compliance and much more The Master Guide to Controllers' Best Practices should be on the bookshelf of every controller who wants to ensure the well-being of their organization.